Impacts of seasonal ambient temperature and humidity on meat quality characteristics of sheep and beef longissimus thoracis muscles - Amri, Issa Al; kadima, Isam T.; Ajmib, Dawood S. Al; Alkindia, Abdulaziz; Sawadc, Alaa A.; Hamaeda, Ahmed; Nasser, Amira (Emirates Journal of Food and Agriculture, 2021)
The effects of seasonal temperature and humidity on meat quality characteristics of sheep (12 months of age) and beef cattle (24 months of age) were investigated. Samples of longissimus thoracis (500 g) muscle were randomly collected from 96 sheep and 48 beef cattle between November 2018 and October 2019. All the meat samples were kept in the chiller at 4-5ºC for 48 h. The samples were collected over a 12-month period and this period was divided into two seasons based on ambient temperature and relative humidity in Basrah region. Theses seasons were named: Cool Season (November to March with average temperature of 23.0±1.54ºC and 59.0±1.75% relative humidity) and Hot Season (April to October with average temperature of 40.5±1.77ºC and 53.5±5.98 relative humidity). The ultimate pH (pHu), expressed juice, cooking losses, shear force, sarcomere length, myofibrillar fragmentation index and colour lightness (L*), redness (a*), and yellowness (b*) parameters were determined. The effect of the season on meat quality characteristics of the Longissimus thoracis muscle from both species was found to be significant (P<0.05). The hot season muscle samples had significantly (P<0.05) higher pHu values, longer sarcomere length, higher myofibrillar fragmentation index with significantly (P<0.05) lower shear force values than the muscle samples collected during the cool season. Sheep and beef longissimus thoracis muscles from the hot season group had significantly (P<0.05) darker meat than that those of the cold season group, based on L*, a* and b* colour measurements. The present findings indicated that hot temperature (>40ºC) leads to heat stress in sheep and cattle, which increased the muscle pHu and influenced other related meat properties. These findings will assist meat producers to improve meat quality parameters by slaughtering livestock at early hours of the day. Hot temperature has also an impact on animal welfare.